Classroom interaction in selected high school chemistry classes - Tezon, Adelaida Chiu (1977)
The purpose of the study was to describe and analyze the verbal interaction between teachers and students in high school Chemistry classes. To describe and analyze the classroom interaction, Bellack Interaction Analysis Scheme was used. Findings showed that there was a significant difference in class interaction among the phases of the lecture session as well as that in the laboratory session. A significant difference was found between the class interaction in the lecture session and laboratory session. The pedagogical moves took up most of the interaction followed by the substantive logical moves and instructional-logical moves. Very little analytical emphasis and evaluative emphasis was found in both sessions although all the groups observed were subject-centered and teacher-dominated.